PEMANFAATAN AQUAPONIK SEBAGAI TEKNOLOGI BUDIDAYA IKAN NILA DAN SAYURAN YANG MENDUKUNG PERTANIAN BERKELANJUTAN DI DESA KAYANGAN, KECAMATAN KAYANGAN, KABUPATEN LOMBOK UTARA - Azis, M Abdul; Widianti, Heny; Sanhuri, Sanhuri; Ranesa, Sulhan Salma; Anggraini, Syarifa Ayu; Mizwar, Zulham; Berliana, Cok Gea; Lestari, Nur Ayu; Kalia, Ragil Alfarizi; Sahrani, Rani; Sriasih, Made (Jurnal Wicara, 2023)
This introduction to aquaponic planting techniques aims to provide examples of the application of advanced and sustainable agricultural technology to the people in Kayangan village, Kayangan sub-district, North Lombok district (KLU). This activity was carried out from December 2022 to February 2023 at the Bagek Kembar hamlet, Kayangan. The fish used were 60 days old fish seeds with a size of 10 cm x 5 cm which were reared in a 4x3 m tarpaulin container. The plant growth media used is in the form of used foam taken from one of the residents' houses with a size of 5 cm. Placement of the planting media uses used plastic cups and used bottles as containers for placing plastic cups. The vegetables used in making this aquaponics are mustard greens, lettuce and pakcoy. The nutrients used to support plant growth are in the form of fish manure and some additional organic nutrients which are made independently using organic waste from the kitchen. The results of using aquaponic technology as a cultivation technology show that the plants grow but the leaves of the plants turn yellow and the fish in the pond can grow large.